Federalizing Embryo Transfers: Taming the Wild West of Reproductive Medicine? - Daar, Judith (Columbia Journal of Gender and Law, 2012)
This article addresses the oft-spoken urban myth that the field of assisted reproductive technologies (ART) is a wholly unregulated medical subspecialty, leaving cowboy physicians to abuse vulnerable patients and disregard the well-being of ART-induced offspring. The birth of octoplets in January 2009 fueled this myth and launched a campaign to regulate the field by restricting the number of embryos allowed for transfer in any single IVF cycle. This article critiques the merits of a federal law codifying embryo transfer limits in the provision of infertility care. Drafting a federal embryo transfer law is easy enough, but assuring enforcement by regulators and compliance by physicians and patients presents near insurmountable barriers. Even if such a law set out sensible clinical guidelines on the number of embryos to transfer, validating that practitioners have complied with statutory standards may require invading patient privacy in a wholly distasteful manner. Moreover, data collected on the effectiveness of civil fines in the regulatory setting suggest rampant undercollection, casting doubt on fine-based penalty’s capacity to deter banned conduct. Still other data suggests that criminal penalties fare no better, as both prosecutors and juries are reluctant to penalize a physician who, in good faith, responds to a patient’s plea for help. Compliance with embryo transfer limits are in doubt not just because traditional penalty structures are ineffective, but because patients and physicians are incentivized by the high cost and low reimbursement rates for infertility care to prefer more embryos be transferred to maximize the chances for a live birth. When multiple births, particularly twins, is a preferred outcome based on financial constraints, looking to a stand-alone embryo transfer law to curb the high rate of multiples will have little effect. Instead, this article argues that now is the time to ease the financial burden by including infertility care in the package of essential health benefits being developed under the 2010 Patient Protection and Affordable Care Act. Matching the burden of embryo transfer limits with the benefit of coverage will have a real and lasting impact on the public health concerns that legitimately coalesce around multiple births.